The national COVID-19 vaccination campaign targeting the extremely vulnerable: the Florence Medical Oncology Unit experience in patients with cancer. (July 2022) - Pino, Maria S.; Cheli, Simone; Perna, Marco; Fabbroni, Valentina; Giordano, Clara; Martella, Francesca; Lanini, Fabio; Ribecco, Angela S.; Scoccianti, Silvia; Bacci, Carlotta; Baldazzi, Valentina; Bertolini, Ilaria; et al.
Abstract: Background: International and national oncology societies had released recommendations in favor of COVID-19 vaccination in cancer patients. In the context of the national vaccination campaign targeting the so called extremely vulnerable, we aimed to assess the safety and efficacy of the mRNA vaccines in a cohort of 623 patients. Methods: Between March 26 and April 04, 2021, the Pfizer and BioNTech BNT162b2 mRNA and the Moderna mRNA-1273 vaccines were given as a two-dose prime-boost regimen. Starting on September 25th 2021 a third dose was offered to patients in whom a suboptimal immunogenicity with COVID-19 vaccination could be expected. Safety assessments were performed by phone call 7 days after each dose. Electronic health records were accessed to review demographic information, disease history, treatment detail, and outcome events of participants patients'. Findings: No toxicities were reported in 63.7%, 54%, and in 48.7% patients with cancer after each dose. Mild-to-moderate pain at the injection site was the most commonly adverse event. After the second dose, 46% of the 610 patients reported toxicity, with more systemic side-effects observed. Fever was reported in 45% of patients, with a temperature ≥ 38 °C in 21.4% of them. Of the 335 patients receiving a third vaccine dose, 51% reported toxicity, with 13% of patients reporting more than one effect. Logistic regression analysis reported mixed results, with limited variables or categories reporting a significant odd ratio. The type of vaccine reported a significant value at first dose (OR = 0.12; CI 0.52, 0.26; p  = 0.00). Thirty-four cases of COVID-19 infection were reported with only one patient requiring a short-term hospitalization for monitoring. Interpretation: The safety profile of the mRNA vaccines does not raise any specific concerns and support prioritization of vaccination for cancer patients. Highlights: COVID-19 vaccination is recommended in patients with cancer. We observed a first dose-refusal rate of 4.5%. No safety concerns have emerged in our cohort of patients. After two-dose prime-boost vaccination 6 cases of COVID-19 infection were reported.